1991
DOI: 10.1007/bf00039742
|View full text |Cite
|
Sign up to set email alerts
|

The scale-up of plant cell culture: Engineering considerations

Abstract: The enormous versatility of plants has continued to provide the impetus for the development of plant tissue culture as a commercial production strategy for secondary metabolites. Unfortunately problems with slow growth rates and low products yields, which are generally non-growth associated and intracellular, have made plant cell culture-based processes, with a few exceptions, economically unrealistic. Recent developments in reactor design and control, elicitor technology, molecular biology, and consumer deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 97 publications
(126 reference statements)
2
16
0
2
Order By: Relevance
“…This observation is also applicable to the case of the Wave bioreactor, in which even though the inoculum was only of 40 F 0.3 g of cells, the inoculum/culture medium relation was also 1/10. These results indicate that the improvement in product yield was mainly due to the immobilization effect, which agrees with the inverse relationship between cell growth and secondary metabolite accumulation in plant cell cultures (Taticek et al, 1991). In a study on the kinetics of growth and paclitaxel yield in cell suspension cultures of T. cuspidata, Fett-Neto et al (1994) observed that the taxane levels decreased with the enhancement of the respective cell biomass.…”
mentioning
confidence: 56%
“…This observation is also applicable to the case of the Wave bioreactor, in which even though the inoculum was only of 40 F 0.3 g of cells, the inoculum/culture medium relation was also 1/10. These results indicate that the improvement in product yield was mainly due to the immobilization effect, which agrees with the inverse relationship between cell growth and secondary metabolite accumulation in plant cell cultures (Taticek et al, 1991). In a study on the kinetics of growth and paclitaxel yield in cell suspension cultures of T. cuspidata, Fett-Neto et al (1994) observed that the taxane levels decreased with the enhancement of the respective cell biomass.…”
mentioning
confidence: 56%
“…Plant cells in suspension culture are derived from callus tissues and tend to form aggregates and large clumps due to the failure of the daughter cells to separate from the parent cells after division [119] and the secretion of extracellular polysaccharides may also contribute to increased cell adhesion [120]. Size distribution of aggregates is dependent on plant host species, method of inoculum preparation, cell growth stage, medium composition, bioreactor types and culture conditions.…”
Section: Aggregation and Rheological Properties Of Suspended Plant Cementioning
confidence: 99%
“…There are mainly two problems with respect to the scaling up of plant cell cultures-hydrodynamic stress on the cells and an insufficient supply of nutrients (Taticek et al 1991). A sufficient nutrient supply requires high agitation and aeration, which subsequently place high hydrodynamic forces on cells.…”
Section: Resultsmentioning
confidence: 99%